Practices for Retaining Employees in the Indian Private Banking Sector - Dr. Naresh Sachdev; Nancy Khanna (Journal of Advanced Research in Economics and Business Management, 2024)
The Indian banking industry is growing fast and needs talented workers. One of the biggest challenges for banks is recruiting and retaining staff. Attrition in India's banking industry ranks third. Research on retention strategies and banking industry factors is scarce for private banks. Employee retention strategies in select private banks are studied. HDFC and ICICI banks are among the top five private banks surveyed. It identifies the retention factors and processes that influence employees' decisions to stay with the bank, analyses the similarities in retention strategies across select private banks, groups the banks by similarities, and interprets the relationship between demographics and satisfaction with banks' retention efforts. Descriptive statistics and single proportion test, ANOVA, Chi-square, Rank sum method, Post Hoc test, and paired comparison are used to analyse primary data. Salary, training and development, bonuses, workplace relations, and Medi-claim benefits influence private sector bank employees' decisions to stay. Bank employees expect rewards for their work, reasonable goals, and better communication to stay motivated and work there.